Rattus argentiventer ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
671. Ricefield Rat Rattus argentiventer French: Rat des rizieres / German: Reisfeldratte / Spanish: Rata de arrozal Taxonomy. Epimys rattus argentiventer H. C. Robinson & Kloss, 1916, Pasir Ganting, west coast of Sumatra, Indonesia. R. argentiventer is in the R. rattus species group, although additional sampling of lessstudied species is needed to fully resolve its placement and that of other species in the genus. Monotypic. Distribution. C Laos, Vietnam, C & S Cambodia, SC Thailand, Malay Peninsula, Singapore, Sumatra, Borneo, Java, Bali, and many smaller offshore Is. Introduced into the Philippines (Luzon, Mindoro, Negros, Cebu, and Mindanao Is), Sulawesi, Lesser Sundas (Lombok, Sumbawa, Sangeang, Komodo, Rintja, Flores, Adonara, Lembata, Alor, Sumba, Timor, and Tanimbar Is), New Guinea, and possibly Seram I. Descriptive notes. Head-body 136-230 mm, tail 149-210 mm, ear 16-24-5 mm, hindfoot 30-41 mm; weight 52-239 g. The Ricefield Rat is medium-sized and similar to the Losea Rat (R. losea), ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 834, DOI: 10.5281/zenodo.6887260 ...